In Situ Test of Grouting Reinforcement for Water-Enriched Sandy Gravel Ground in River Floodplain - Jinxing Lai; Zhihua Feng; Junling Qiu; Jianxun Chen; Haobo Fan (Advances in Materials Science and Engineering)
The performance of the ground treatment is always critical for a tunnel excavated in unstable stratum. Laodongnanlu Xiangjiang Tunnel (Changsha, China) across the Xiangjiang River will be constructed in a sandy gravel ground which is characterized by loose structure, extensive porosity, elevated sensitivity, poor stability, and a high groundwater table. Permeation grouting will be employed to improve the bearing capacity and mitigate groundwater movement into the excavation. In order to seek suitable injection parameters and grouting method, a field trial of vertical grouting was conducted in the sandy gravel stratum in river floodplain. A series of tests focusing on grout material, grouting sequence of boreholes, injection pressure, and grouting volume were performed to improve the sandy gravel mass strength and reduce water permeability. The examination of the results obtained during water pressure testing and core drilling on completion of the grouting trial successfully demonstrated that the specified injection criteria had led to an expected effect. Grouting control method of this saturated sandy gravel stratum was concluded after the test, which would contribute to the future pregrouting work during the tunnelling.